Improved methods for structural wind engineering - Knapp, Graham Anthony (2007)
This thesis describes research examining the use of computational fluid dynamics (CFD) in structural wind engineering. It looks in particular at steady and unsteady RANS simulations and Detached Eddy Simulation and their use in the calculation of structural loads on static bluff building structures. Previous research across structural wind engineering and CFD is reviewed and critically examined with respect to structural engineering. CFD simulations are performed and compared with published flow data for simple cubes. Loading studies are performed for a complex building and the results compared with wind tunnel studies used in the structural design of the building.